TRANSIÇÃO DE CUIDADOS DA INTERNAÇÃO HOSPITALAR AO DOMICÍLIO:ESTUDO DE MÉTODO MISTO - Liasse Monique de Pinho Gama (2023)
Introduction: Transition of care can be understood as the transfer of information aiming at the continuity of care provided in the transfer of users in the different sectors within the same institution, or in the different types of health services; it is a strategy that aims to ensure continuity of care after hospital discharge. The actions developed during the transition of care can reflect on the quality of life and the safety of patients, becoming a complex and dynamic process, which requires effective communication between the people involved in the various formations, skills and experiences. In this perspective, the needs of the patient/family member to develop continuous and complex care at home in favor of their quality of life and survival stand out. Therefore, nursing interventions should promote knowledge and care capacity to those who experience them in the process of transition from hospital to home. Objective: To analyze the transition of inpatient care to home care. Method: This is a mixed methods study, with concomitant transformative approach with greater qualitative weight (quan + QUAL), guided by the Transitions Theory. Data were collected throughout the months of April and September 2022. Four data collection instruments were used, namely: a patient and family characterization script; Barthel index; Care Transitions Measure instrument (CTM-15); and a patient and family interview script. Data collection was divided into two stages. In the first stage, patients and family members were recruited during hospital admission, and in the second, a visit was carried out between ten and 30 days after hospital discharge. Analysis of quantitative and qualitative data was done through the integration of these stages by the strategy of analysis of the merged data, based on the representation of the theoretical model of Transitions by Afaf Meleis. All ethical precepts were respected. Results: 26 patients and 18 family members participated in the study. The nature of the transitions was permeated by new appointments and readmission. Among the inhibiting and facilitating conditions, family dynamics, low income and primary care follow-up stand out; the response pattern of the transition was unsatisfactory (MTC score 59.23). The failure in verbal and nonverbal communication between professionals and patients was the main element that influenced patient safety in the transition of care, emphasizing the absence of a written care plan and incomplete or insufficient guidance. Conclusion: The transition from inpatient care to home care was inadequate. The discharge plan was a practice for a safe transition of care and will be recognized when nurses incorporate and value this assignment. It is considered necessary to create strategies that contemplate an effective, safe and responsible discharge planning, one which promotes better results for the recovery of well-being and quality of life after discharge. Keywords: Transition of care. Discharge planning. Patient safety. Study with mixed methods. Nursing.